The Power Of Literature: Can The Dead Speak? - Bootheina Majoul (The Journal of Studies in Language, Culture and Society)
Since the beginning of recorded history, literature is the finest means of human expression. Its tool is the language through which it creates alternative universes representing facts or fiction. Whether imagined or real, narratives have the power to voice silence, unveil verity and become thus receptacles of an ever present past. Indeed, Literature empowers; it acts as memory preserved within closed pages, forgotten then remembered every time a book is read. It survives time and revives reminiscences; it is “a record of human consciousness” (Lodge 10). It is a safe space for writers, a shelter, a secret keeper; but also, a counter space and alternative one for readers since it delivers lessons from the past that migrate, and offer possibilities. The “dead” text, the corpse of the narrative (as well as corpse narratives) provides post death truths that survive us, for the next generation, for history, for the archive. That inanimate object helps people understand the world. In fact, Literature is power otherwise. By means of language it gives voice to the voiceless, the marginalize and the oppressed. Literary dissent is the most peaceful way to exert power and make views, pain, and (in)justice heard. This paper will dig into the power of Literature to change history through stories; it will examine selected texts and different literary genres to highlight the plight of words, and narratives’ transformative nature/power.